Pemahaman Islam dan Kristen Menurut Pandangan M. Talbi ‘Iyalullah: Afkar Jadidah Fi ‘Alaqah Al–Muslimin’: As the object of Muslim-Christian dialogue, M. Talbi studied the heritage of the spiritual value of a religion that follows the biblical tradition - Rakhmawati, Ellya; Abdullah, M. Amin; Suyati., Tri (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
In M. Talbi’s view, we see a more practical dimension than in Arkoun’s view, and so on. M. Talbi describes dialogue as one of the most important parts for humanity to be religious and humane, to be fully committed to the will of God. Christians and Muslims together make peace and justice between two religious communities. As the object of Muslim-Christian dialogue, M. Talbi studied the heritage of the spiritual value of a religion that follows the biblical tradition. M. Talbi also explained that from the Qur’anic perspective, dialogue is a religious issue commanded by Revelation. The entire Revelation as M. Talbi sees in the Qur’anic sentence, commands the people, the Prophet, the Muslims, to engage in dialogue with men in general, and especially with believers from the religion of the book. The essence of religious understanding of dialogue is "reconciliation or the organization of new relationships".